Prioritizing Areas for King County Metro Transit’s Feeder-to-Fixed Route Flexible Services: A Preliminary Approach for the Systematic Locational Prioritization of Future Services - Munkel, Daniel (My University, 2020)
This work presents an approach for systematically prioritizing areas in King County, Washington for future feeder-to-fixed route (F2FR) flexible service. This approach is meant to inform service planning processes for King County Metro Transit (Metro) by providing a framework for the analytical process as well as for the policy considerations that underpin the inputs to the analysis. These analytical inputs are informed by Metro’s Mobility Framework, Metro staff expertise, and academic and practice literature. The analysis identifies specific criteria and methods for Metro to prioritize areas within the county for future F2FR flexible transit services, and then employs spatial analysis to develop a ranked list of priority areas based on these components. The authors are particularly interested in highlighting the policy priorities embedded in the weighted criteria that make up this analysis, and how varying the analytical inputs alters the prioritized ranking of areas throughout the county. Ultimately, this work seeks to present an analytical framework for planning for F2FR flexible services that is closely tied to a robust set of policy and service priorities.
Thesis (Master's)--University of Washington, 2020
Keywords: Equity; Flexible Transit Service; King County; On-Demand; Transportation Planning; Urban Planning; Transportation; Urban planning; Public policy; Urban planning